SYNTHESIS OF UREA CONTROLLED RELEASE FERTILIZER (CRF) ENCAPSULATED BY SILICA MEMBRANE - LANTANG (NIM : 13707066); Dosen Pembimbing : Dr.Ir.Bambang Sunendar, OLIVIA
Urea fertilizer is one type of fertilizer which the consumption is increasing every year due to high nitrogen content in it. Generally, the fertilizer nutrients can be absorbed by plants only 60-70% of the total nutrients of urea so that the excessive use of fertilizers will have a negative impact on the environment. Controlled release fertilizer (CRF) is one of technology that was developed to optimize the absorption of fertilizer nutrients by plants. Synthesis of CRF in this study is made from urea fertilizer as core with silica membranes as shell that prepared by sol-gel method using sodium silicate precursor, and additives chitosan and polyethylene glycol (PEG) 6000. Encapsulation process is done by spraying the coating on the surface of the fertilizer solution and followed by drying process with oven. Characterization of SEM, FTIR, and BET conducted to determine the effect of increasing concentrations of PEG 6000 and spraying time of the solution membrane. Characterization results indicate that increasing spraying time of the membrane from 5 to 10 minutes will increase the thickness, specific surface area, volume and size of membrane pores with 20% PEG concentration by 6.3 μm, 0.26 m2/g, 0156 x 10-3 cc/g and 0.68 ÃƒÂ…, and membrane with 30% PEG by 39.3 μm, 0.34 m2/g, 0232 x 10-3 cc/g and 1.86 ÃƒÂ…. Increasing concentrations of PEG from 20 to 30% would increase the specific surface area, pore volume and diameter of the membrane sprayed for 5 minutes by 0.08 m2/ g, 0043 x 10-3 cc/g and 0.1 ÃƒÂ…, and sprayed for 10 minutes by 0.16 m2/g, 0119 x 10-3 cc/g and 1.28 ÃƒÂ…. From measurements of the rate of nutrients release in water, it was found that the time required by the encapsulation to release all of fertilizer nutrient is very fast, 60-90 seconds, and the silica membrane is water soluble.